Environmental Impacts of Mining on Bundelkhand Region of Uttar Pradesh, India - Amit Pal, Gayatri Singh (Recent Research in Science and Technology, 2010)
Surface mining creates more pollution in comparison to underground mining. This paper highlights the impact of mining on air, water and human health in and around the mining areas of Jhansi, Bundelkhand region, India. The possibility of leaching contaminants from the ore material kept in the open ground or from the wastages or degraded ore material produced during the mining processes may contaminate the groundwater in the study area. The mining activity comprising drilling, blasting, loading of waste, transport of overburden and crushing of ore is having considerable impacts on the air environment and well being of living organism. Mining either by opencast or by underground methods damages the water regime and thus causes a reduction in the overall availability of water in and around the mining areas. This study showed that the ground water and surface water was alkaline in nature. Mineral handling, mineral preparation and associated activities mainly contribute RSPM and SPM to the surrounding environment. The minimum and maximum value of RSPM and SPM was 173.1 mg m-3 to 212 mg m-3 and 462.4 mg m-3 to 521.3 mg m-3 respectively. High levels of suspended particulate matter increase respiratory diseases such as chronic bronchitis and asthma causing health hazards to the exposed population. Metals like Cd, Mn, Pb, Cu, Fe and Si concentrations were found to the above permissible limit at some places in different seasons and may cause health hazards in existing environment.